1970
DOI: 10.1042/bj1190067
|View full text |Cite
|
Sign up to set email alerts
|

Osmometry with single Sephadex beads

Abstract: 1. The measurement of osmotic pressure by means of a single bead of Sephadex (Edmond, Farquhar, Dunstone & Ogston, 1968) has been made more precise by immobilizing the bead on a fine needle. The design, calibration and use of the osmometer are described. 2. The method is particularly suitable for measuring high osmotic pressures in solutions of high-molecular-weight solutes, which must not penetrate the Sephadex to a significant extent. 3. With Sephadex G-50 the limit of precision is about 1.5cmH(2)O and the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

1972
1972
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…Earlier investigators also analyzed the influence of smoking, alcohol consumption and oral contraceptives intake. Fibrinogen levels were found to be significantly higher in male smokers than non-smokers (Howell, 1970 andOgston, 1970). ( Williamand phillips2000) .biochemical parameters we see in the results in Table, (2) showed that there were a significant increase serum estrogen in patients of breast cancer women compared to the control group.…”
Section: Discussionmentioning
confidence: 92%
“…Earlier investigators also analyzed the influence of smoking, alcohol consumption and oral contraceptives intake. Fibrinogen levels were found to be significantly higher in male smokers than non-smokers (Howell, 1970 andOgston, 1970). ( Williamand phillips2000) .biochemical parameters we see in the results in Table, (2) showed that there were a significant increase serum estrogen in patients of breast cancer women compared to the control group.…”
Section: Discussionmentioning
confidence: 92%
“…1 presents results obtained with three different polysaccharides studied on the larger column. Since each of these solutes is sufficiently large to be essentially excluded from the gel phase in the presence of salt Ogston & Wells, 1970;Wells, 1972), the variation in elution volume is a direct measure of changes in the void volume. In turn, such changes must arise as a consequence of shrinkage of gel beads and it is therefore relevant to examine the results in terms of eqn.…”
Section: Methodsmentioning
confidence: 99%
“…In such quantitative studies, the methods employed to allow for the effects of concentration dependence are entirely analogous to those used to correct for frictional effects in sedimentation velocity. However, the effect in chromatography is likely to be osmotic in origin Nichol et al, 1969;Ogston & Wells, 1970). The present work explores this postulate further.…”
mentioning
confidence: 99%
“…Dextran 500 was from Pharmacia, batch T 5406. Solutions were made and their concentrations measured as described by Ogston & Wells (1970). Titration of solutions (see below) showed a very low content of Cl-ion.…”
Section: Experimental Materialsmentioning
confidence: 99%